2019
DOI: 10.25124/ijies.v3i01.29
|View full text |Cite
|
Sign up to set email alerts
|

IT Services Quality Measurement Using IT SERVQUAL at University X

Abstract: Information technology plays a major role to enhance service activities in organizations as well as in higher educational institutions / universities.  A special unit (Sisfo) at University X is dedicated to handles daily technology-based services. Every year the performance of the unit is evaluated to increase customer satisfaction and yet the result is contradictory. Using balanced scorecard, the result showed that the unit's performance is in a good category, but when it comes to the satisfaction questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…An element is definitely better than another element 2, 4,6,8 The values between the two value are close…”
Section: Analytical Hierarchy Processmentioning
confidence: 93%
See 1 more Smart Citation
“…An element is definitely better than another element 2, 4,6,8 The values between the two value are close…”
Section: Analytical Hierarchy Processmentioning
confidence: 93%
“…The definition of service quality is which the service fulfills its specifications [7]. According to the Six Sigma Methodology, quality is the degree or measurement to which a set of characteristics fulfils requirements that can influence customer satisfaction [8]. The rapid growth of Internet makes service quality be the main choice in online transactions.…”
Section: Literature Study 21 Electronic Service Qualitymentioning
confidence: 99%
“…The performance of these eleven service attributes needs to be improved by Bhinneka Shuttle Mekar Wangi because the services currently provided are still not able to meet the expectations of its customers. Service quality is an individual's opinion on how service is provided and affects customer satisfaction [26].The results of the RESCA and Kano integration data processing obtained 11 True Customer Needs and were included in weak attribute category because they had a negative CSC value which indicated that the services provided by the company were still unable to meet the satisfaction of its customers and needed to improve the quality of its services. The Kano model classifies different components in service quality that are influenced or shaped by customer perceptions of service quality.…”
Section: True Customer Needmentioning
confidence: 99%
“…Despite annual evaluations through balanced scorecards and satisfaction questionnaires, the results were contradictory. Therefore, a reevaluation was conducted using the Servqual method, concluding that immediate action was needed in dimensions such as inadequate physical facilities like hardware and software, and processes related to academic activities, such as system access failures, card recording errors, and student attendance list inaccuracies [27]. This research contributes to the field by advocating for the use of the Servqual method in measuring IT service performance at a university to avoid incongruent results.…”
Section: Related Workmentioning
confidence: 99%